2020
DOI: 10.1007/s42452-020-03647-5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content estimation in the Mexico City Street dust: an inter-method comparison and Pb levels assessment during the last decade

Abstract: Elemental concentrations measured in 482 street dust samples from different urban and conurbated areas of Mexico City obtained using a portable energy-dispersive X-ray fluorescence spectrometer are reported. The data quality of eight different elements commonly used in pollution studies is evaluated, calculating the data precision and accuracy obtained with this handheld equipment. Precision for the various elements analyzed ranges between 1.2 and 15.9%, which can be considered as adequately precise for portab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…There is a great concern due to Pb contamination worldwide and, in particular, in Mexican cities, since it is the metal with the highest concentrations in outdoor dust and represents an ecological and children’s health risk (Aguilera et al 2022 ). Pb concentrations in this study are lower than those found in a previous study in Mexico City (Morales et al 2020 ). In 2016 the average concentration of Pb was 122 mg/kg, while in 2020 (the sampling year for this study) the average concentration was 74.7 mg/kg.…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…There is a great concern due to Pb contamination worldwide and, in particular, in Mexican cities, since it is the metal with the highest concentrations in outdoor dust and represents an ecological and children’s health risk (Aguilera et al 2022 ). Pb concentrations in this study are lower than those found in a previous study in Mexico City (Morales et al 2020 ). In 2016 the average concentration of Pb was 122 mg/kg, while in 2020 (the sampling year for this study) the average concentration was 74.7 mg/kg.…”
Section: Resultscontrasting
confidence: 91%
“…This XRF equipment was the same one used to measure the concentrations of the metals in the present study. The average Zn in street dust from 2016 (sampling year in Morales et al 2020 ) to 2020 sampled for this research has increased by 13%, 495.5 and 569.4 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations